Space- and time-resolved diagnostics of the ENEA EUV discharge-produced-plasma source used for metrology and other applications. (25th November 2015) - Bollanti, S.; Di Lazzaro, P.; Flora, F.; Mezi, L.; Murra, D.; Torre, A.
Abstract : A discharge-produced-plasma (DPP) source emitting in the extreme ultraviolet (EUV) spectral region is running at the ENEA Frascati Research Centre. The plasma is generated in low-pressure xenon gas and efficiently emits 100-ns duration radiation pulses in the 10–20-nm wavelength range, with an energy of $20~\text{mJ}/\text{shot}/\text{sr}$ at a 10-Hz repetition rate. The complex discharge evolution is constantly examined and controlled with electrical measurements, while a ns-gated CCD camera allowed observation of the discharge development in the visible, detection of time-resolved plasma-column pinching, and optimization of the pre-ionization timing. Accurately calibrated Zr-filtered PIN diodes are used to monitor the temporal behaviour and energy emission of the EUV pulses, while the calibration of a dosimetric film allows quantitative imaging of the emitted radiation. This comprehensive plasma diagnostics has demonstrated its effectiveness in suitably adjusting the source configuration for several applications, such as exposures of photonic materials and innovative photoresists.